The consequences of perceived risk and objective knowledge for consumers' investment behavior. Issue 4 (December 2017) - Munnukka, Juha; Uusitalo, Outi; Koivisto, Veera-Juulia
Abstract Knowledge and risks have a focal role in consumer behavior. However, studies on consumers' perceive risks in decision situations and the influence of objective knowledge and experience on risk perceptions, consumers' attitudes and behavioral intentions are scarce. This paper introduces and tests a novel conceptual model that shows how consumers' objective financial knowledge and investing experience affect their future investment intentions mediated by perceived risks, and attitudes toward investing. The data were analyzed using structural equation modeling. The proposed model fits the data and accounts for attitudes and intentions to investing. This study advances knowledge by directly measuring the behavior-related objective knowledge and experience. We also suggest new insights into the risk concept by showing that consumers perceive five types of risk in investing context and objective financial knowledge and investment experience has varying effects on different risks types, attitudes and intentions. The results also show significant gender differences.